IMPLEMENTASI MODEL PEMBELAJARAN M-APOS DAN METODE MOORE TERMODIFIKASI UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIKA MAHASISWA - abdul aziz saefudin; Kintoko Kintoko (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The study of this research is to analyze differences in the students’ mathematical proving ability that follow the learning model of M-APOS learning and the conventional learning in Matrix Algebra course. This research is quasi-experiment with non-equivalent control group design. The population of this research is all students who take the Matrix Algebra the course in odd semester Academic Year 2017/2018 as many as 120 students and purposive sampling samples are as many as 79 students. The research instrument used a mathematical proving ability test. Data analysis used descriptive statistics and nonparametric statistics (Kruskal-Wallis test). The results of this study are: the average of students’ mathematical proving ability that follow the M-APOS learning model and modified Moore method are significantly better than students follow conventional learning in Matrix Algebra course; there is a difference of improving the mathematical proving ability of students following the M-APOS learning model, modified Moore method, and conventional learning; the improvement in the mathematical proving ability of students following the M-APOS learning model and modified Moore method is significantly better than students who follow conventional learning in Matrix Algebra courses. The improvement of students' mathematical proving ability that follows with the M-APOS learning model is better than students who follow with the modified Moore method and conventional learning models. While the improvement of students’ mathematical ability that follow with the modified Moore method is better than students who follow conventional learning.